Pengaruh Model Pembelajaran Picture And Picture Berbantuan Media Video Terhadap Hasil Belajar IPA - sukinah, nur; rati, ni wayan; japa, i gusti ngurah (Jurnal Ilmiah Sekolah Dasar, 2018)
Problem discussed in this research is, whether there is a significant effect of picture and picture technique video-based media towards students’ science achievement of fourth grade of Buleleng district primary schools cluster XI. This study aimed at discovering the effect of picture and picture technique video-based media towards students’ science achievement of fourth grade of Buleleng district primary schools cluster XI academic year 2017/2018. This was a quasi-experimental research. There were 167 students from all fourth grade of Buleleng district primary schools cluster XI academic year 2017/2018 as the population of this study. The sample was chosen using random sampling technique. The samples of this study were 31 students from fourth grade of MIN 2 Buleleng and 38 students from SD LAB Undiksha. The data collection was done through test. The instrument of the test was an objective test with 40 questions. The obtained data were analysed descriptively and inferentially (t-test polled variance). Hypothesis testing showed that t observed = 3.86 > t critical value = 1.996 significance 5%. It means that there was a difference of science learning achievement in experiment group and control group. The result of the mean of experimental group was 23,19 is higher than the mean of control group was 19,87. Thust, it can be concluded that learning using picture and picture learning video-based media gave a positive effect towards students’ science achievement in fourth grade of Buleleng district primary schools cluster XI academic year 2017/2018.